New essays on Pareto's economic theory - Bruni, Luigino, 1966-; Montesano, Aldo. (London ; New York : Routledge, 2009)
This edited collection brings together a selection of essays from some of the most authoritative scholars of Pareto, who discuss the relevance of Pareto’s economics in the context of the present theoretical debate.
&#x000A
Introduction / Aldo Montesano and Luigino Bruni -- Pareto's methodological project / Luigino Bruni -- Pareto and contemporary economic theory / John S. Chipman -- Choice, preference and rationalizability in Pareto's theory of economic behaviour / Marco Dardi -- Walras and Pareto on the meaning of the solution concept in general equilibrium theory / Franco Donzelli -- Equilibrium without prices : a central issue in Pareto's Manuale / Antonio Gay -- Pareto's influence on modern economics / Roberto Marchionatti -- Vilfredo Pareto and contemporary economics : social equilibrium, fiscal decentralisation and economic growth / Michael McLure -- An analytical-epistemological reconstruction of the genesis of Pareto's Manuale di economia politica / Fiorenzo Mornati -- Pareto on Ricardo and Bastable's comparative costs / Alberto Zanni -- The Paretian theory of ophelimity in closed and open cycles / Aldo Montesano -- Order of consumption and measurability of utility / Paolo Scapparone.
"Simultaneously published in the USA and Canada by Routledge."
Includes bibliographical references and index.
lje 23/04/13
Loans
Keywords: Pareto, Vilfredo, -- 1848-1923.; Economics -- Italy -- History -- 19th century; Equilibrium (Economics); Income distribution; Neoclassical school of economics